2002
DOI: 10.1016/s0248-4900(02)00018-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation and differential regulation of the cardiac gap junction proteins connexin 43 and connexin 40

Abstract: Gap junction channels provide the basis for the electrical syncytial properties of the heart as a communicating electrical network. Cardiac gap junction channels are predominantly composed of connexin 40 or connexin 43. The conductance of these channels (g(j)) can be regulated pharmacologically: substances which activate protein kinase C, protein kinase A or protein kinase G may alter Cx43 gap junction conductance. However, for PKC, this seems to be subtype specific. Thus, antiarrhythmic peptides can enhance g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 107 publications
(124 reference statements)
3
29
2
1
Order By: Relevance
“…Although Cx43 might also be directly phosphorylated by PKA, most evidence argues against this view (20,35). Furthermore, in contrast to the current observations, cAMP commonly increases Cx43 gap junctional permeability in other preparations (20,35,51), albeit reducing message for Cx43 in rat Leydig cells (53). In addition, intracellular cAMP had no acute effect on Cx43 and Cx40 gap junctions expressed in HeLa cells (33).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Although Cx43 might also be directly phosphorylated by PKA, most evidence argues against this view (20,35). Furthermore, in contrast to the current observations, cAMP commonly increases Cx43 gap junctional permeability in other preparations (20,35,51), albeit reducing message for Cx43 in rat Leydig cells (53). In addition, intracellular cAMP had no acute effect on Cx43 and Cx40 gap junctions expressed in HeLa cells (33).…”
Section: Discussioncontrasting
confidence: 93%
“…Cx43 is known to be phosphorylated by protein kinase C, MAP kinase, and the pp60src kinase (35). Although Cx43 might also be directly phosphorylated by PKA, most evidence argues against this view (20,35). Furthermore, in contrast to the current observations, cAMP commonly increases Cx43 gap junctional permeability in other preparations (20,35,51), albeit reducing message for Cx43 in rat Leydig cells (53).…”
Section: Discussioncontrasting
confidence: 80%
“…Recently, novel protein interacting with Cx43 in astrocytes has been identified -brain-derived integrating factor-1 (BDIF-1) which is probably involved in regulating of astroglial activity (Ito et al, 2011). Pharmacological modulation of Cx43 can be achieved by various compounds (Dhein et al, 2002). T. Nakase et al (Nakase & Naus, 2004) reported that the activation of astrocytes associated with an increase in the expression and activity of connexin 43 protects neurons from ischemia-induced damage.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Mediators like endothelin-1, angiotensin-II, TGFbeta, VEGF, and cAMP have been shown to increase Cx43 [4]. Pharmacologically changing endothelin-1, angiotensin-II, TGF-beta, VEGF, and cAMP et al into positive substances to mediate cardiac gap junction conductance for the treatment and prevention of cardiac diseases is also a good strategy.…”
Section: Reformed Mediators Likementioning
confidence: 99%